Speech text of the 2nd International Conference on Modern Languages & Applied Linguistics (ICMAL) 2023 / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
My utmost appreciation also goes to ICMAL's main collaborators from Lombok, Indonesia, and the strategic partners and endorsers from Thailand, Indonesia, India, and Malaysia for the endless support given to ICMAL 2023. These collaborative efforts have made ICMAL 2023 a more unique and attractive event.